Femtosecond and UV inscribed grating characterization in photonic crystal fibres: optimization for sensing applications - Yiangou, Eleni; Themistos, Christos; Komodromos, Michael; Kalli, Kyriacos; Christodoulides, Paul; Koutsides, Charalambos (My University, 2012)
Photonic crystal fibres (PCF) and more commonly microstructure fibres, remain interesting and novel fibre types and when suitably designed can prove to be "ideal" for sensing applications, as the different geometrical arrangement of the air holes alters their optical wave-guiding properties, whilst also providing tailored dispersion characteristics. This impacts the performance of grating structures, which offer wavelength encoded sensing information. We undertake a study on different air hole geometries and proceed with characterization of fibre Bragg and long period gratings, FBG and LPG, respectively that have been inscribed (using either a femtosecond or ultraviolet laser system) within different designs of microstructured fibre that are of interest for sensing applications
Keywords: Fibers; Photonic crystals; Optical engineering